PROBLEMS OF DISABILITY AND TREATMENT ADHERENCE IN HIV-INFECTED PATIENTS - E. R. Isaeva; A. D. Buzunova; S. A. Buzunova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Introduction. This study focuses on the problem of early disability of patients with HIV-infection and treatment adherence and dispensary observation. Material and methods. The clinical and anamnestic analysis of 1136 out-patient records and medical records of patients registered at Saint-Petersburg State Budgetary Institution of Healthcare “Center for Prevention and Control of AIDS and Infectious Diseases” and directed at medical and social examination was carried out. In addition, using the test methods we investigated the psychosocial characteristics of 76 patients who applied to the psychologist before the beginning of antiretroviral therapy, and assessed the treatment adherence a year after the start of treatment. Results. The results of the study indicated the increase in the proportion of patients at advanced stages of the disease, increased detection of HIV in older age groups. Late diagnosis of the disease is the cause of temporary disability and early disability of patients with HIV infection. The dynamics of the number of disabled persons due to HIV infection increasing. Men need more time to decide on dispensary care than women. The majority of patients with are men of working age, identified or sought medical care at the late stages of the disease. Women are more attentive to their health and have more complex treatment adherence than men. The interrelations of psychological and somatic characteristics with the level of adherence to medical recommendations were found.